Street fentanyl use: Experiences, preferences, and concordance between self-reports and urine toxicology - Daniulaityte, Raminta (Int J Drug Policy, 2019)
BACKGROUND: Conducted in Dayton, Ohio, the study aims to characterize user knowledge and experiences with non-pharmaceutical fentanyl-type drugs (NPFs) and compare self-reports with urine toxicology for NPFs and heroin. METHODS: Between May 2017- January 2018, 60 individuals who self-reported heroin/NPF use were interviewed using structured questionnaire on sociodemographics, NPF and other drug use practices. Unobserved urine samples were collected and analyzed using: 1) liquid-chromatography-tandem mass spectrometry (LC-MS/MS)-based method (Toxicology lab) to identify 34 fentanyl analogues, metabolites, and other synthetic opioids; 2) immunoassay-based method to screen for opiates (heroin). Sensitivity, specificity and Cohen’s kappa were calculated to assess agreement between self-reports and urine toxicology. RESULTS: The sample was 52% female, and over 90% white. Almost 60% reported preference for heroin, and 40% for NPF. Participants endorsed a number of ways of distinguishing heroin from NPF, including appearance (88.3%), effects (76.7%), taste (55%), and information provided by dealers (53.3%). Almost 80% felt confident they could distinguish heroin from NPF, but knowledge about fentanyl analogues was limited. LC-MS/MS testing identified 8 types of NPFs and/or metabolites. Over 88% tested positive for NPFs, including 86% fentanyl, 48% carfentanil, 42% acetyl fentanyl. About 47% screened positive for opiates/heroin, and all of them were also positive for NPFs. When comparing self-reported use of NPF to urine toxicology, sensitivity and specificity were relatively high (84% and 83.3%, accordingly), while Cohen’s Kappa was 0.445, indicating fair agreement. Sensitivity and specificity were lower for heroin (77.8% and 50.0%, accordingly), and Cohen’s Kappa was 0.296, indicating low agreement between self-reports of heroin use and urine toxicology. DISCUSSION: Nearly 90% of the study participants tested positive for NPF-type drugs. Participants were more likely to over-report heroin use and underreport NPF use. The majority had little knowledge about fentanyl analogues. Study findings will inform development of novel harm reduction approaches to reduce overdose mortality.